PENYULUHAN MANFAAT PENGOLAHAN MENTIMUN SEBAGAI MINUMAN SEHAT DI KAMPUNG BUAH WAGIR LOR - Fery setiawan; Saiful Nurhidayat; Wahyudi Wahyudi; Ayok Ariyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2022)
The development of village potential is something that must be done to improve progress in a village. Wagir Lor Village, which is one of the village areas traversed by the tourists of Ngebel Ponorogo Lake, has natural potential and a fairly strategic village location. However, there are several problems faced, such as the lack of community understanding of village potential, lack of management in established business entities, lack of innovation in local commodities and lack of utilization of village wealth for health. With the establishment of a Fruit Market in Wagir Lor village, it is felt necessary to provide understanding and training on the management of village business entities such as the fruit market. In addition, the community also needs to be provided with training to process Cucumbers into medicinal drinks. Besides being able to provide additional innovation to local commodities, this training is also expected to overcome natural problems in the health sector in Wagir Lor Village. With good management of the Fruit Market and starting with the processing of Cucumbers into health drinks for the residents of Wagir Lor Village.